The wilt pathogen induces different variations of root-associated microbiomes of plant - Tao, Jiemeng; Yu, Shizhou; Jin, Jingjing; Lu, Peng; Yang, Zhixiao; Xu, Yalong; Chen, Qiansi; Li, Zefeng; Cao, Peijian (Frontiers in Plant Science, 2022)
Root-associated compartments, including the rhizosphere, rhizoplane, and endosphere, live with diverse microbial communities which profoundly affect plant growth and health. However, a systematic understanding of the microbiome assembly across the rhizosphere, rhizoplane, and endosphere under pathogen invasion remains elusive. Using 16S high-throughput sequencing, we studied how bacterial wilt disease affected the variation and assembly of the three continuous root-associated microbiomes of tobacco. The results indicated that microorganisms were gradually filtered from the rhizosphere to the endosphere. With the pathogen invasion, the rhizosphere, rhizoplane and endosphere microbiomes selected and recruited different beneficial bacterial taxa. Some recruited bacteria were also identified as keystone members in networks (i.e., Bosea in the endosphere). The microbiomes of endosphere and rhizoplane were more sensitive to plant disease than the rhizosphere microbiome. Still, response strategies of the rhizoplane and endosphere to disease were obviously different. Microbial networks of the rhizoplane became complex in diseased samples and genes involved in sporulation formation and cell cycle were enriched. However, microbial networks of the diseased endosphere were disrupted, and functional genes related to nitrogen utilization and chemotaxis were significantly increased, indicating the importance of nitrogen resources supply of plants for the endosphere microbiome under pathogen invasion. Our results provide novel insights for understanding the different responses of the root-associated microbiomes to plant disease.